2016
DOI: 10.1007/s10653-016-9830-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and human health risk assessment of heavy metal contamination in soil of a municipal solid waste dump in Uyo, Nigeria

Abstract: The study assessed the levels of some heavy metals in soils in the vicinity of a municipal solid waste dumpsite with a view to providing information on the extent of contamination, ecological risk of metals in the soils and human health risk to the residents in Uyo. Soil samples were collected in rainy and dry seasons and analyzed for metals (Pb, Cd, Zn, Mn, Cr, Ni and Fe) using atomic absorption spectrometry. The concentrations of heavy metals (mg/kg) at the dumpsite in rainy season were Pb (9.90), Zn (137), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(73 citation statements)
references
References 32 publications
7
61
2
3
Order By: Relevance
“…PHEs from industrial activities and agricultural fertilization management accumulate continuously after entering the soil and migrate in different systems (such as water systems and crops), thereby entering the human body through the food chain, resulting in harm to human health [3,65]. Besides, compared with daily average exposure, non-carcinogenic risk index and carcinogenic risk index, it can be found that children are more vulnerable to PHEs in soil than adults (Figure 8), which is similar to previous research results [44,60,65]. It is mainly because the children's immune resistance is much lower than that of adults, which is more sensitive to environmental pollution.…”
Section: The Phes Health Risk In Coastal Tideland Reclamation Areasupporting
confidence: 87%
See 1 more Smart Citation
“…PHEs from industrial activities and agricultural fertilization management accumulate continuously after entering the soil and migrate in different systems (such as water systems and crops), thereby entering the human body through the food chain, resulting in harm to human health [3,65]. Besides, compared with daily average exposure, non-carcinogenic risk index and carcinogenic risk index, it can be found that children are more vulnerable to PHEs in soil than adults (Figure 8), which is similar to previous research results [44,60,65]. It is mainly because the children's immune resistance is much lower than that of adults, which is more sensitive to environmental pollution.…”
Section: The Phes Health Risk In Coastal Tideland Reclamation Areasupporting
confidence: 87%
“…If CR < 10 −6 , it will neglect the carcinogenic risk to human health. 10 −6 < CR < 10 −4 is considered an acceptable range and CR > 10 −4 is viewed as unacceptable [44].…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…The increased amount of HM in soil leads to greater uptake by plants that can reduce plant growth, biomass, photosynthesis, crop yield, and quality in plant [57]. From a biological point of view, the top soil is the most active zone of soil that accumulates a large amount of toxic metals that poses serious concern to the environment [49,58,59].…”
Section: Hm Stress and Its Impacts On Plantsmentioning
confidence: 99%
“…The geoaccumulation index (Igeo) was distinguished into seven classes. Igeo ≤ 0, class 0, unpolluted; 0 < Igeo ≤ 1, class 1, from unpolluted to moderately polluted; 1 < Igeo ≤ 2, class 2, moderately polluted; 2 < Igeo ≤ 3, class 3, from moderately to strongly polluted; 3 < Igeo ≤ 4, class 4, strangle polluted; 4 < Igeo ≤ 5, class 5, from strongly to extremely polluted; and Igeo > 5, class 6, extremely polluted [26,27].…”
Section: Index Of Geoaccumulation (Igeo)mentioning
confidence: 99%
“…The following terminology were used for the potential ecological risk index: Er i >40, low potential ecological risk; 40 ≥ Er i >80, moderate potential ecological risk; 80 ≥ Er i >160, considerable potential ecological risk; 160 ≥ Er i >320, high potential ecological risk; and Er i ≤ 320, very high ecological risk and The following terminology are used for the potential ecological risk index: RI > 150, low ecological risk; 150 ≥ RI > 300, moderate ecological risk; 300 ≥ RI > 600, considerable ecological risk; and RI ≤ 600, very high ecological risk [29].…”
mentioning
confidence: 99%